La fin de la diversité ? Démantèlement jurisprudentiel du Voting Rights Act aux États-Unis - Olivier Richomme (Revue LISA)
This article analyses the jurisprudential deconstruction of the 1965 Voting Rights Act by the Supreme Court over the past thirty years. This deconstruction completes that of other race-conscious public policies by the Court (Affirmative Action, school desegregation). Both parties have concentrated their ideological and partisan conflict on the right to vote and have used the law as their weapon of choice. As a consequence, the process of political representation in the US is still very much encumbered by the weight of history. Paradoxically, this Voting Rights Act deconstruction might be an opportunity for voting rights advocates.